2019
DOI: 10.1101/852137
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A classification of functional pitcher types in Nepenthes (Nepenthaceae)

Abstract: We classify Nepenthes species into 12 functional pitcher types, based on combinations of traits that appear to comprise different syndromes for capturing nutrients, usually from animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…At the same time, this location's soil is acidic and poor in nitrogen. This habitat follows the opinion of Cheek et al (2019), which states that Nepenthes can generally live and develop in large numbers on nutrient-poor soils, especially nitrogen deficiency.…”
Section: Nepenthes Abiotic Environmental Datamentioning
confidence: 66%
See 1 more Smart Citation
“…At the same time, this location's soil is acidic and poor in nitrogen. This habitat follows the opinion of Cheek et al (2019), which states that Nepenthes can generally live and develop in large numbers on nutrient-poor soils, especially nitrogen deficiency.…”
Section: Nepenthes Abiotic Environmental Datamentioning
confidence: 66%
“…Therefore, the larger pitcher size can accommodate more insects (Buch et al 2015;Dančák et al 2022;Tarigan et al 2021;Wang and Zhou 2014). On the other hand, the upper pitcher size is generally smaller so that it is lighter so that if exposed to the wind, the pitcher will not fall easily (Cheek et al 2019;Handayani and Hadiah 2019). Based on the measurements of mouth length, mouth width, cap length, and cap width in N. gracilis and N. eustachya, it was found that there were variations in the size of the mouth and lid of the pitcher.…”
Section: Morphological Parameters Nepenthesmentioning
confidence: 99%
“…Convergence of pitcher morphology is recorded in other cases in the genus ( Thorogood, Bauer & Hiscock, 2018 ). Recently, 12 functional pitcher types have been recognised, each postulated to target capture of nutrients from animals (sometimes plants) in a different manner ( Cheek, Jebb & Murphy, 2020 ). Nepenthes maxima and Nepenthes maximoides fall under pitcher type 2 (‘narrow-funnel’ Cheek, Jebb & Murphy, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The shared pitcher morphology of this specimen with that of Nepenthes maxima appears due to convergence, not due to phylogenetic proximity. Convergence of pitcher morphology is recorded in other cases in the genus (Thorogood et al, 2018), where 12 functional pitcher types have been recognised, each postulated to target capture of nutrients from animals (sometimes plants) in a different manner (Cheek et al, 2020a). Nepenthes maxima, and also the species represented by Curran s.n., fall under pitcher type 3 ("visco-elastic traps" Cheek et al, 2020a).…”
Section: Introductionmentioning
confidence: 95%